Coaxial microwave assisted hydrodistillation of essential oils from five different herbs (lavender, rosemary, sage, fennel seeds and clove buds): Chemical composition and thermal analysis. (February 2016) - González-Rivera, José; Duce, Celia; Falconieri, Danilo; Ferrari, Carlo; Ghezzi, Lisa; Piras, Alessandra; Tine, Maria Rosaria
Abstract: Lavender, sage, rosemary, fennel seed and clove bud essential oils (EOs) were isolated using a microwave-assisted Clevenger-type device, where the microwaves are applied by means of a coaxial antenna and by conventional hydrodistillation (HD). The yield and chemical composition of EOs were analyzed as a function of the microwave (MW) extraction time. A complete chemical characterization was performed by gas chromatography (GC) and gas chromatography–mass spectrometry (GC-MS) analysis. The analysis of the thermal behavior and stability of the EO were performed by thermogravimetry (TG) and thermogravimetry coupled to infrared spectrometry (TG-FTIR). Thermal analysis showed that the EO thermal behavior is described by the evaporation of its main compounds. The most volatile EO was the rosemary, while clove EO was the most thermally stable. The coaxial MWHD extraction leads to a high concentration of oxygenated monoterpenes, different product selectivity, energy savings, and reductions in heating time compared to the EO obtained by conventional HD. The coaxial antenna method allows the scale-up to industrial level without any limit of power and size. Industrial relevance: In literature there are many articles that show the effectiveness and usefulness of the microwave in the chemical and food processing. This technology offers the possibility of faster and more uniform heating, and gives rise to processes that are not completely identical to the methods of conventional heating. However, the application of microwave technology in industry is very limited. This is due to the difficulty in industrial scale-up of microwave ovens. In fact, the use of microwave ovens or resonant cavities involves drawbacks that limit their use. In particular, they have irregular distributions of electromagnetic fields, forming hot-spot, non-uniformity of irradiance, difficulty using common sensors. In addition, the depth of irradiation is limited to a few centimeters. In this article we present an application of an innovative method to irradiate microwave, which uses coaxial antennas. The use of such antennas removes many of the constraints of microwave ovens. For example, it is possible to use glass reactors, use several antennas, immerse the antennas in depth in a liquid overcoming the limits of the depth of penetration and thus treat high volumes. We believe that this technology is mature for the industrial application. Highlights: Lavender, sage, rosemary, fennel and clove EOs isolated by two methodologies Coaxial MWHD yields EOs with high concentrations of oxygenated monoterpenes. Thermal behavior and stability study of EOs by TG and TG-FTIR techniques Energy and time saving as a result of the coaxial MWHD approach to EO isolation Easy industrial scale-up